Microscopic analysis of Tilia cordata - Babeshina, L (Fundamental and Experimental Biology, 2025)
The raw material base for medicinal plant resources can be expanded both by introducing new plant species into practical use and by utilizing additional plant organs of species already in use. The flowers of Tilia cordata are a valuable type of medicinal raw material; however, their collection is constrained by a short flowering period. The leaves of this species also exhibit pharmacological activity, making them a promising independent source of medicinal plant material. This article presents the results of a microscopic analysis of Tilia cordata leaves. Anatomical examination was performed on dried leaves, with an assessment of the structural features observed in surface preparations and cross sections. The leaf was found to be hypostomatic, with the main epidermal cells having straight or wavy walls. On the abaxial surface, four types of trichomes were identified: glandular, forked, capitate, and stellate. A crystalline coating was observed along the leaf veins. In cross section, the leaf is dorsiventral, with a single-layered palisade mesophyll, a 2-3- layered spongy mesophyll, mucilage channels, and druses of calcium oxalate. Diagnostic microscopic features have been identified that may be used in the preparation of a pharmacopoeial monograph.